Protocol for multi-scale light microscopy/electron microscopy neuronal imaging in mouse brain tissue - Kenta Yamauchi; Takahiro Furuta; Shinichiro Okamoto; Megumu Takahashi; Masato Koike; Hiroyuki Hioki (STAR Protocols, 2022)
Summary: An imaging technique across multiple spatial scales is required for extracting structural information on neurons with processes of meter scale length and specialized nanoscale structures. Here, we present a protocol combining multi-scale light microscopy (LM) with electron microscopy (EM) in mouse brain tissue. We describe tissue slice preparation and LM/EM dual labeling with EGFP-APEX2 fusion protein. We then detail ScaleSF tissue clearing and successive LM/EM imaging. Our protocol allows for deciphering structural information across multiple spatial scales on neurons.For complete details on the use and execution of this protocol, please refer to Furuta et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.